CHI '13 Extended Abstracts on Human Factors in Computing Systems 2013
DOI: 10.1145/2468356.2468531
|View full text |Cite
|
Sign up to set email alerts
|

The potentials of in-situ-projection for augmented workplaces in production

Abstract: Interactive projections have been around for more than a decade. We measured their potentials for augmented workplaces in production. For this purpose we built the prototype of an assistive system projecting instructions directly into the workspace (in situ). While it can be applied in every production environment, the system was first implemented and tested where it is needed the most: in a sheltered work organization employing persons with impairments.It could be shown that the assembly times could be slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Due to the recent growing interest in smart manufacturing and Industry 4.0 [18], [19], studies on recognizing and supporting factory work using sensor technologies [20], [21] have been attracting attention.…”
Section: Related Workmentioning
confidence: 99%
“…Due to the recent growing interest in smart manufacturing and Industry 4.0 [18], [19], studies on recognizing and supporting factory work using sensor technologies [20], [21] have been attracting attention.…”
Section: Related Workmentioning
confidence: 99%
“…Korn et al [3] showed that projected information is helpful for impaired persons in performing manual assembly work. They focused on projecting information directly onto work spaces but they did not look into changing work hand movements to match those of experts.…”
Section: Related Workmentioning
confidence: 99%
“…For gamification to be useful and accepted in industrial production contexts, it has to be discrete and "stay in the back". This results in the following requirements for an ideal implementation, which have partly been described in previous work [19] :…”
Section: Requirementsmentioning
confidence: 99%